Pengaruh Pelayanan dan Harga Sewa Kamar Terhadap Keputusan Tamu Menginap dengan Pendekatan Syariah di Hotel Narapati Indah Syariah Bandung - Gandara Catur Prasetya; Nunung Nurhayati; Nandang Ihwanudin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study is motivated by the low occupancy rate of Narapati Indah Syariah Hotel Bandung in recent months, allegedly influenced by service quality and room rental prices. Based on service marketing theory, good service and appropriate pricing can affect consumers’ decisions to purchase or use services. This research aims to analyze the effect of service quality and room rental prices on guests’ decisions to stay. The research method employs a quantitative approach with a positivism paradigm and a survey method. The study population includes all hotel guests in January 2024, totaling 561 people, with a sample of 85 respondents selected through purposive sampling. Primary data were collected using questionnaires and analyzed using multiple linear regression after validity, reliability, and classical assumption tests. The results indicate that service quality and room rental prices have a positive and significant effect, both partially and simultaneously, on guests’ decisions to stay. These findings highlight the importance of improving service quality and adjusting competitive prices to increase the hotel’s room occupancy rate.